Plant diversity of the Xuan Son national park (Phu Tho province) - Hoi, Tran Minh; Phuong, Vu Xuan (Academia Journal of Biology, 2014)
The flora of the Xuanson national park (Phutho province) is very rich and diverse, including 180 families, 680 genera and 1,217 species of 6 vascular plant phyla. The taxon distributions of these taxa are different. The Magnoliophyta phylum has 151 families (83.88%), 633 genera (93.08%) and 1,130 species (92.85%); the Polypodiophyta has 22 families (12.22%), 38 genera (5.58%) and 74 species (6.08%); the Pinophyta has 3 families, 4 genera and 5 species; the Lycopodiophyta has 2 families, 3 genera and 6 species; the smallest taxa are Equisetophyta and Psilotophyta with 1 family, 1 genus and 1 species each. Four species are new recorded for the flora of Vietnam: Aristolochia fangchii C. Y. Wu (Aristolochiaceae); Quercus sichourensis (Hu) C. C. Huang & Y. T. Chang (Fagaceae); Pseudostachyum sp. (Poaceae), distributed at altitude of 300-800 m in the Dzu village and the Ten mountainfoot; Rhododendron euonymifolium LÐvl. (Ericaceae). In Magnoliophyta, the Magnoliopsida class has 127 families (84.10%); 526 genera (83.09%) and 947 species (83.80%), that is much higher in numbers of families, genera and species than in the Liliopsida class. Among 180 families, there are 35 families with 1 species, 71 families with 2-4 species, 33 families with 5-9 species, 28 families with 10-19 species and 13 families with more than 20 species. The Euphorbiaceae is the most diverse family (60 species), followed by Rubiaceae (49 species), Fabaceae, Moraceae.... There are 26 genera with more than 5 species, made up 4% compared to the total genera of the flora but with 186 species (15.28% the total species of the flora); these genera are Ficus (24 species), Ardisia (13 species), Piper and Polygonum, each with 9 species; Diospyros, Elaeocarpus, Hedyotis, Psychotria and Dendrobium, each with 7 species; Begonia, Bauhinia, Desmodium, Maesa, Helicia, Solanum, Callicarpa, Clerodenrun, Carex, Cyperus and Dioscorea, each with 6 species and lastly Tectaria, Pteris, Schefflera, Garcinia, Rhododendron and Syzygium, each with 5 species. There are 40 endangered species (representing 3,4% of the total species of the flora of the Xuanson national park) listed in the Red Data Book of Vietnam (2004), the IUCN Red List of Threatened Plants (2001) and the Governmental Decree 32/2006/N§/CP dated March. 30. 2006, that need to be given priority for conservation and protection. Useful plant resources comprise medicinal plants (665 species); timber plants (202 species); vegetables and edible fruits (132 species); ornamental plants (90 species); aromatic plants (26 species); bamboo, rattan, fern, jute (9 species); forages (12 species); oleiferous plants (9 species) and poisonous plants (8 species).